Multi-Parameter Model-Based Polarimetric Calibration for Dual-Coded Spectral Polarization Imaging System - Jiayu Wang; Haodong Shi; Yingchao Li; Qiang Fu; Yingjie Zhao; Huilin Jiang (Photonics, 2023)
A polarization analysis method based on a multi-parameter model is proposed to address the polarization effect analysis and calibration requirements of a dual-coded snapshot spectral polarization imaging system. A full-link polarization effect model for a spectral polarization imaging system is established that includes a digital micromirror array (DMD), prism grating prism (PGP), micro-polarizer array detector (MPA), and multi-film. The influence of parameters such as the refractive index, incident angle, grating refractive index, constant, prism refractive index, vertex angle, multi-layer film complex refractive index, and film thickness on the optical transmittance of the system are analyzed. Using a dynamic data exchange mechanism to perform full-link, full-FOV, and full-pupil ray tracing on the optical system, the polarization effect distribution of the system under different degrees of polarization (DOP) and wavelengths is obtained. A calibration experiment for the controllable incident wavelength and DOP using narrowband filters and glass stacks is established. The experimental results show that in the 420 nm, 532 nm, and 635 nm wavelength bands, the MSEs of the calibrated values are 1.3924 × 10−4, 1.6852 × 10−4, and 1.6735 × 10−4, respectively. It is proven that the calibration method based on a multi-parameter model is feasible. Finally, the spectral polarization image at 532 nm is calibrated. The contrast ratio of metallic aluminum is calibrated from 7.13 to 15.33. This study provides a theoretical basis for the analysis and calibration of polarization effects in a dual-coded snapshot spectral polarization imaging system.